Reciprocal evolution of the cerebellum and neocortex in fossil humans - Weaver, Anne H. (National Academy of Sciences, 2005)
Human brain evolution involved both neurological reorganization and an increase in overall brain volume relative to body mass. It is generally difficult to draw functional inferences about the timing and nature of brain reorganization, given that superficial brain morphology recorded on fossil endocasts is functionally ambiguous. However, the cerebellum, housed in the clearly delineated posterior cranial fossa, is functionally and ontologically discrete. The cerebellum is reciprocally connected to each of 14 neocortical regions important to human cognitive evolution. Cerebellar volume varies significantly relative to overall brain volume among mammalian orders, as well as within the primate order. There is also significant diachronic variation among fossil human taxa. In the australopithecines and early members of the genus Homo, the cerebral hemispheres were large in proportion to the cerebellum, compared with other hominoids. This trend continued in Middle and Late Pleistocene humans, including Neandertals and Cro-Magnon 1, who have the largest cerebral hemispheres relative to cerebellum volume of any primates, including earlier and Holocene humans. In recent humans, however, the pattern is reversed; the cerebellum is larger with respect to the rest of the brain (and, conversely, the cerebral hemispheres are smaller with respect to the cerebellum) than in Late Pleistocene humans. The cerebellum and cerebral hemispheres appear to have evolved reciprocally. Cerebellar development in Holocene humans may have provided greater computational efficiency for coping with an increasingly complex cultural and conceptual environment.